The Effects of Latrepirdine on Amyloid-ß Aggregation and Toxicity - Porter, T.; Bharadwaj, P.; Groth, David; Paxman, A.; Laws, S.; Martins, R.; Verdile, Giuseppe (2016)
© 2016 - IOS Press and the authors. All rights reserved. Latrepirdine (DimebonTM) has been demonstrated to be a neuroprotective and cognition improving agent in neurodegenerative diseases that feature protein aggregation and deposition, such as Alzheimer's disease (AD). The accumulation of amyloid-ß (Aß) protein aggregates is a key event in the neurodegenerative process in AD. This study explores if latrepirdine modulation of protein aggregation contributes to its neuroprotective mechanism of action. Assessment of neuronal cell death showed that there was a significant reduction in lactate dehydrogenase release at an equimolar ratio of Aß:latrepirdine and with lower concentrations of latrepirdine. The ability of latrepirdine to alter the formation of Aß42 aggregates was assessed by thioflavin-T fluorescence, western immunoblotting and atomic force microscopy (AFM). Despite showing a reduction in thioflavin-T fluorescence with latrepirdine treatment, indicating a decrease in aggregation, immunoblotting and AFM showed a modest increase in both the formation and size of Aß aggregates. The discrepancies between thioflavin-T and the other assays are consistent with previous evidence that cyclic molecules can interfere with thioflavin-T binding of amyloid protein preparations. The ability of latrepirdine to modulate Aß aggregation appears to be independent of its neuroprotective effects, and is unlikely to be a mechanism by which latrepirdine offers protection. This study investigates the effect of latrepirdine on Aß aggregation, and presents evidence suggesting that caution should be applied in the use of thioflavin-T fluorescence based assays as a method for screening compounds for protein aggregation altering properties.